Influence of Reference Groups and Positive eWOM on Consumer Responses to Green Products - Sajjanit, Chonlada (Creative Business and Sustainability Journal, 2020)
The purpose of this study is to examine the relationship among reference group influence, positive electronic word of mouth (eWOM) messages, consumers’ attitudes and purchase intention for green products. A survey-based empirical study was conducted with 307 consumers through purposive sampling method. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were applied for data analysis. The results indicate that normative referents i.e. family members and friends enhance consumers’ positive attitudes towards buying green products, leading to purchase intention. Comparative referents such as celebrities are found not to impact consumers’ responses to green products significantly. Positive eWOM recommendations i.e. specialized eWOM, social eWOM, and miscellaneous eWOM have positive effects on attitude towards green products, and that positive attitudes, in turn, influence purchase decisions. This study integrates the body of knowledge among consumer behavior, digital marketing and green marketing. This contributes to additional knowledge of social influence factor in green marketing literature, which has been underresearched. The research findings could encourage green companies to improve their marketing campaigns that support relationship formation and information sharing on various internet platforms among consumers.